Companies’ perception toward manufacturing execution systems - Adil Aramja; Oualid Kamach; Rachid Elmeziane (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The use of information systems in manufacturing sector is very crucial to reach a high level of operational excellence and improve companies’ competitiveness. The use of such systems will definitely increase in the upcoming years, considering the digitalization strategies. Manufacturing execution systems gained a lot of attention in recent years due to showcased benefits in production management operations. Companies that adopted such systems witnessed an increase in process efficiency and enhancements with regards to cost savings and products quality. This paper seeks to analyze what makes the usage of manufacturing execution systems successful among manufacturing companies. We analyzed how the integration capabilities of such systems with other business applications and the company profile impact their usage and consequently the perceived benefits. A case study was conducted with 51 manufacturing companies and data were analyzed using partial least square structural equation modeling technique. The results confirmed the positive and significant impact of the company profile and solution integration capabilities on system usage. In addition, a ranking of solution modules importance for companies was also provided.